Ser e Náusea: ontologia e literatura em Sartre - Favero, Carlos Henrique (2025)
The main objective of this dissertation is to present the concept of freedom advocated by Jean-Paul Sartre. For this purpose, it was necessary to address the terms substantiating this subject since its ontology, constraining it to the human being in question until the literary-philosophic engagement. The reading of Being and Nothingness by commentators and literary works of Sartre has grounded the theoric unfoldings for explaining the constant relation of human beings to the world that surrounds them. This dissertative path has been sectioned into three chapters. The first addresses the conceptual pillars for safe progress of understanding the being in the world: the relationship between being and phenomenon, consciousness, nothing, for themselves and within themselves. In this sense, it is possible to point to freedom with an ontologic basis that helps build Sartre’s phenomenological ontology. The second one aims to explain the freedom facing the Facticity and helps to understand that even if human beings are radically free, they have in their actions the intermediate of conditions which reality entails, such is the case of the being concerned and of their relation of the for-themselves to the in-themselves. For this reason, it seeks to enlighten human actions before the world, whether from bad faith or in original life projects. It is in this scenario that the urge to highlight freedom as a pure possibility, such as a constant strain throughout existence. Chapter three examines selected literary texts by Sartre, arguing for the presence of philosophical themes consistent with his Being and Nothingness. In this regard, it has been expatiated on an engaged freedom from the writer´s bond with the reader. Therefore, there is no division between philosophy and literature in the works analyzed. The philosophical literature of Sartre, with the understanding of the characters and their situations, allows us to deepen even more the concept of freedom issued in the previous chapters.